Free MoS2 Nanoflowers Grown on Graphene by Microwave-Assisted Synthesis as Highly Efficient Non-Noble-Metal Electrocatalysts for the Hydrogen Evolution Reaction - Cao, Jiamu; Zhang, Xuelin; Zhang, Yufeng; Zhou, Jing; Chen, Yinuo; Liu, Xiaowei (PloS one, 2016)
Advanced approaches to preparing non-noble-metal electrocatalysts for the hydrogen evolution reaction (HER) are considered to be a significant breakthrough in promoting the exploration of renewable resources. In this work, a hybrid material of MoS2 nanoflowers (NFs) on reduced graphene oxide (rGO) was synthesized as a HER catalyst via an environmentally friendly, efficient approach that is also suitable for mass production. Small-sized MoS2 NFs with a diameter of ca. 190 nm and an abundance of exposed edges were prepared by a hydrothermal method and were subsequently supported on rGO by microwave-assisted synthesis. The results show that MoS2 NFs were distributed uniformly on the remarkably reduced GO and preserved the outstanding original structural features perfectly. Electrochemical tests show that the as-prepared hybrid material exhibited excellent HER activity, with a small Tafel slope of 80 mV/decade and a low overpotential of 170 mV.